Whole genome analysis, detoxification of ochratoxin a and physiological characterization of a novel Bacillus velezensis MM35 isolated from soil - Fengru Xu; Fengru Xu; Fengru Xu; Mengmeng Tang; Mengmeng Tang; Mengmeng Tang; Zhihao Yang; Zhihao Yang; Zhihao Yang; Chengshui Liao; Chengshui Liao; Chengshui Liao; et al. (Frontiers in Microbiology)
Ochratoxin A (OTA) is a significant global contaminant that poses severe challenges to food safety and public health. This study aims to isolate the OTA-degrated probiotics and evaluate genetic and biological characteristic. Here, The degradation rate of a new strain named Bacillus velezensis MM35 isolated from soil was the highest (87.10% within 48 h), and its culture supernatant was the main component of OTA degradation (63.95%) by high performance liquid chromatography. Further investigation revealed that the extracellular enzyme that degrades OTA in the culture supernatant of MM35 may be a small molecule enzyme with certain heat resistance. Genome-wide analysis showed that MM35 contains a cluster of carboxypeptidases encoding OTA-degrading potential, and had good metabolic and catalytic synthesis ability, and strong application potential in the synthesis and degradation of carbohydrates and proteins. A variety of secondary metabolites with antibacterial properties, such as non-ribosomal peptide synthetase and terpenoids, were identified in its metabolites. Consistent with the predicted results, MM35 showed various enzyme production characteristics such as cellulase and xylanase. Furthermore, MM35 could inhibit the growth of a variety of pathogenic bacteria, and showed high co-aggregation ability to Escherichia coli and Salmonella typhimurium. In addition, MM35 has certain tolerance to harsh environments such as strong acid, bile salt, and high temperature. Additionally, the adhesion rate of MM35 was 5.4%, and the invasion rate was 2.1% in IPEC-J2 cells. In summary, the data suggest MM35 isolated strain has high OTA degradation efficiency, antibacterial activity and intestinal colonization, which provided a new way for the treatment of OTA contamination in food and feed industries.